1992
DOI: 10.1159/000158940
|View full text |Cite
|
Sign up to set email alerts
|

Altered Aortic Production of 6-Keto-Prostaglandin F<sub>1&alpha;</sub>from Aldosterone-Salt Hypertensive Rats

Abstract: Supersensitivity of vascular smooth muscle to catecholamines in aldosterone-salt hypertensive rats appears to reside beyond the α1-adrenoceptor. The objective of this study was to assess the norepinephrine-stimulated production of arachidonic acid metabolites by aorta from control-salt rats (CSR) and aldosterone-salt hypertensive rats (AHR) to determine whether these metabolites might contribute to the altered sensitivity. Norepinephrine increased in a time-dependent manner the production of 6-keto-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…1981, Uehara et al. 1987, 1990) due to noradrenaline‐induced stimulation of vascular PGI 2 synthesis and release (Jones et al. 1992).…”
Section: Discussionmentioning
confidence: 99%
“…1981, Uehara et al. 1987, 1990) due to noradrenaline‐induced stimulation of vascular PGI 2 synthesis and release (Jones et al. 1992).…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Thus, our data on the enhanced indomethacin-induced BP rise in conscious hypertensive rats, as well as a highly significant positive correlation (Figure 7b) between the indomethacin-induced BP rise and the basal BP level, represent a direct confirmation of the validity of the above data under the in vivo conditions. Interestingly, Jones et al 27 reported that norepinephrine, through its alpha 1 -adrenergic mechanisms, stimulated the in vitro production of PGI 2 , prostaglandin E2 and thromboxane A2 in the aorta of saltloaded rats, and this prostanoid formation was effectively inhibited by indomethacin, which also shifted the contractile dose-response curve to higher norepinephrine concentrations. When we examined the relationships between sympathetic vasoconstriction and prostanoiddependent vasodilatation in our set of experimental animals, we found a highly significant correlation between the magnitude of the pentolinium-induced BP fall and the indomethacin-induced BP rise (r¼0.599, n¼53, Po0.0001), which is in good agreement with the in vitro findings of Jones et al 27 There was a closer correlation between the basal BP and the pentolinium-induced BP fall than with the indomethacin-induced BP rise (Figures 7a and b), supporting the primary importance of sympathetic hyperactivity for the maintenance of high BP.…”
Section: Discussionmentioning
confidence: 99%